Pengembangan Kemampuan Kreativitas Dalam Pembelajaran IPS - Amini, Amini; Sahfitri, Anggi Ayu; Fadillah, Allya; Lubis, Kamalia; Mahyuni, Lela; Abdi, Khoirul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Field applications show that social science education is still mainly at the theoretical level. Even the attitude that social studies education is only